Individual Strategies of Response Organization in Multitasking Are Stable Even at Risk of High Between-Task Interference - Reinert, Roman; Brüning, Jovita (Frontiers in Psychology, 2022)
Recently, reliable interindividual differences were found for the way how individuals process multiple tasks (at a cognitive level) and how they organize their responses (at a response level). Previous studies have shown mixed results with respect to the flexibility of these preferences. On the one hand, individuals tend to adjust their preferred task processing mode to varying degrees of risk of crosstalk between tasks. On the other, response strategies were observed to be highly stable under varying between-resource competition. In the present study, we investigated whether the stability of response strategies also persists with increased risk of crosstalk or whether individuals adjust their choice of response strategy, similar to what has been found at the level of task processing modes. Besides, related differences in multitasking efficiency were assessed. For this purpose, 53 participants performed the Free Concurrent Dual-Tasking (FCDT) paradigm, which allows them to control their task scheduling and response organization. The participants completed the FCDT paradigm under two conditions including task pairs characterized by either low or high levels of risk of crosstalk. The free choice of task scheduling resulted in the previously found distinct response patterns, best described as blocking, switching or response grouping. Remarkably, we did not find any notable adjustments of strategies of response organization to the extent of crosstalk. However, we observed suspected performance decrements of a switching strategy in the condition of high risk of crosstalk. The results suggest that individual strategies of response organization are stable habits. Further, they illustrate disadvantages of switching versus blocking strategies of response organization in case of high task similarity.